Validating 3D two-parameter fracture mechanics for structural integrity assessments - Simpson, C; Tonge, S; Cinar, A; Reinhard, C; Marrow, T; Mostafavi, M (Elsevier, 2018)
In-situ fracture tests were carried out on the I12 beamline at the Diamond Light Source. Four Al-Ti metal-matrix composites (MMCs), with varying combinations of thickness and crack length, were studied to assess for the impact of in-plane and out-of-plane constraint. Synchrotron X-ray computed tomography and synchrotron X-ray diffraction were used to measure total strain and elastic strain respectively. The total strain was calculated via digital volume correlation, with Ti particles within the MMC providing sufficient texture to track the internal displacement vectors in 3D. The total, elastic-plastic strain energy release rate, J total was calculated from 2D slices extracted from the 3D displacement field, with J total reaching a maximum value at the sample surface. It is, however, still unclear whether calculating J total on a slice-by-slice basis provides an accurate representation of strain energy release rate across the crack front; techniques to evaluate the J-integral from the full 3D displacement field are being developed.